The Intention to Use Blockchain in Indonesia Using Extended Approach Technology Acceptance Model (TAM) - Upayana Wiguna Eka Saputra; Gede Sri Darma (CommIT (Communication and Information Technology) Journal, 2022)
Globalization has quickly transformed the economy and society, marked by the rapid integration of data and information, supply chains, and increasingly huge use of technology. The research aims to analyze the level of intention to use blockchain in Indonesia, especially the My-T Wallet developed by Tokoin using the Extended Technology Acceptance Model (TAM) approach. The research modifies the TAM by adding other variables that play an essential role in making decisions about using blockchain. The target population is that the respondents at least know about blockchain developments, in this case, My-T Wallet from Tokoin. The research obtains as many as 103 respondents who fill out the questionnaire through the purposive sampling technique. The data are collected through online surveys and analyzed using the Structural Equation Model (SEM) approach with the SmartPLS software. The findings highlight that the perception of the usefulness of the My-T Wallet application is most strongly influenced by public influence. Meanwhile, perceived ease of use is most influenced by the user interface in My-T Wallet. Then, the intention to use My-T Wallet application is strongly influenced by users’ positive behavior. On the other hand, the level of trust of application users must continuously be increased by paying more attention to government regulations and security aspects.